Clemastine Ameliorates Myelin Deficits via Preventing Senescence of Oligodendrocytes Precursor Cells in Alzheimer’s Disease Model Mouse - Xie, Yuan-Yuan; Pan, Ting-Ting; Xu, De-en; Huang, Xin; Tang, Yong; Huang, Wenhui; Chen, Rui; Lu, Li; Chi, Hao; Ma, Quan-Hong (Frontiers in Cell and Developmental Biology, 2021)
Disrupted myelin and impaired myelin repair have been observed in the brains of patients and various mouse models of Alzheimer’s disease (AD). Clemastine, an H1-antihistamine, shows the capability to induce oligodendrocytes precursor cells (OPCs) differentiation and myelin formation under different neuropathological conditions featuring demyelination via the antagonism of M1 muscarinic receptor. In this study, we investigated if aged APPSwe/PS1dE9 mice, a model of Alzheimer’s disease, can benefit from chronic clemastine treatment. We found the treatment reduced brain amyloid-beta deposition and rescued the short-term memory deficit of the mice. The densities of OPCs, oligodendrocytes (OLs) and myelin were enhanced upon the treatment, while the levels of degraded MBP were reduced, a marker for degenerated myelin. In addition, we also suggest a role of clemastine on preventing OPCs from entering the state of cellular senescence, which was shown recently as an essential causal factor in AD pathogenesis. Thus, clemastine exhibits a therapeutic potential in AD via preventing senescence of OPCs.